Peran Green Economy dalam Meningkatkan Aspek Kesejahteraan Sosial Masyarakat (Studi Literatur) - Novita Rahmawati; I.Ketut Bayangkara (Universitas 45 Surabaya, 2024)
Stochastic Frontier Approach (SFA) is a technique of measuring the level of efficiency with a This study aims to review the role of green economy in improving people's social welfare. Green economy is defined as a sustainable and environmentally friendly economic model that balances economic, environmental, and social aspects. Social welfare is measured by various indicators, such as health, education, income, and security. Based on the literature review, the green economy has the potential to improve social welfare through various mechanisms, including: green job creation, poverty reduction, improved health, improved education quality, improved security. This research also discusses some of the challenges and opportunities in implementing the green economy to improve social welfare. In conclusion, the green economy has significant potential to improve people's social welfare. Effective green economy implementation requires collaborative efforts from various stakeholders, including the government, private sector and civil society.